Genetic variability and principal component analysis in durum wheat germplasm for terminal drought stress - G M, VIJETH; UDAY, GOVINDAREDDY; KRISHNAPPA, GOPALAREDDY; N, SHASHIDHAR (The Indian Journal of Agricultural Sciences, 2025)
Durum wheat (Triticum durum Desf.) is an important species in wheat where drought poses a significant challenge for its productivity and world food security. The study was carried out during winter (rabi) season 2021–22 and 2022–23 at University of Agricultural Sciences, Dharwad, Karnataka to investigate the genetic variability and association between morphological and drought-responsive traits for grain yield in durum wheat collected from International Center for Agricultural Research in the Dry Areas (ICARDA) and International Maize and Wheat Improvement Center (CIMMYT). Pooled analysis of variance revealed highly significant differences (P 0.9, moderately tolerant (18) with STI value 0.8–0.9, and susceptible (130) with STI value < 0.8 based on their sensitivity to drought stress. In the tolerant category, the genotypes GDP2022-246, GDP2022-198, GDP2022-52, GDP2022-216, and GDP2022-47 demonstrated promising performance with good grain yield under moisture stress conditions.